1997
DOI: 10.3109/10715769709097868
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Production After Exposure of Astrocytes and Astrocytic C6 Glioma Cells to Ethanol. Preliminary Results

Abstract: Formation of the alpha-hydroxyethyl radical (CH3 degree CHOH) has already been extensively demonstrated after ethanol metabolism in the liver. Despite favourable conditions, this formation in the brain has remained speculative since there is no direct experimental evidence in intact brain cells. In this preliminary study, the formation of such a radical was observed after exposure of astrocytes and astrocytic C6 glioma cells to ethanol. These cells were studied because astrocyte integrity is essential for norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Fewer studies were conducted in brain, an induction of DNA single-strand breaks was nevertheless observed in rat brain cells after in vivo or in vitro ethanol administration (Singh et al, 1995;Li et al, 2001). Moreover, acetaldehyde, ROS, and a-hydroxyethyl radical, generated by ethanol metabolism (Rashba-Step et al, 1993;Gonthier et al, 1997), are highly reactive and can interact with DNA (Halliwell and Gutteridge, 1999). After acetaldehyde exposure, researchers have thus reported DNA synthesis decreases, DNA single-and double-strand break formation, DNA fragmentation induction, sister-chromatid exchanges and DNA repair enzyme inhibitions on di¡erent cell types (Thompson and Folb, 1982;Obe et al, 1986;Singh and Khan, 1995a; *p50.05, **p50.01 between exposed groups and their respective controls, 12 h or 96 h after exposure (Fishers PLSD test, n = 15 in three independent series).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fewer studies were conducted in brain, an induction of DNA single-strand breaks was nevertheless observed in rat brain cells after in vivo or in vitro ethanol administration (Singh et al, 1995;Li et al, 2001). Moreover, acetaldehyde, ROS, and a-hydroxyethyl radical, generated by ethanol metabolism (Rashba-Step et al, 1993;Gonthier et al, 1997), are highly reactive and can interact with DNA (Halliwell and Gutteridge, 1999). After acetaldehyde exposure, researchers have thus reported DNA synthesis decreases, DNA single-and double-strand break formation, DNA fragmentation induction, sister-chromatid exchanges and DNA repair enzyme inhibitions on di¡erent cell types (Thompson and Folb, 1982;Obe et al, 1986;Singh and Khan, 1995a; *p50.05, **p50.01 between exposed groups and their respective controls, 12 h or 96 h after exposure (Fishers PLSD test, n = 15 in three independent series).…”
Section: Discussionmentioning
confidence: 95%
“…Generating reactive oxygen species through the ethanolinducible cytochrome P450 2E1 (Rashba-Step et al, 1993) and deriving free radicals from ethanol (a-hydroxyethyl radical) (Gonthier et al, 1997) has thus been proposed as a major toxic factor for the brain (Nordmann et al, 1992). The central nervous system is indeed highly susceptible to oxidative damage due to its high oxygen consumption, low levels of antioxidant enzymes and high levels of free iron.…”
Section: Introductionmentioning
confidence: 99%
“…The content of GSH in glial cells is roughly 16 times higher than in neurons (Raps et al, 1989). Thus, it is likely that the low-GSH redox ratios in the corpus mamillare and cerebellum reflect oxidative stress or decreased GSSG reductase activity, both in neurons and glial cells (Gonthier et al, 1997;Montoliu et al, 1995). Alcohol-related changes include white matter loss and neuronal loss in the hypothalamus and cerebellum (Harper, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…The role of oxidative stress and mitochondrial malfunction as a cause of ethanol-induced brain damage has been proven in neuronal (Montoliu et al, 1994;Sun et al, 1997) and glial cell culture experiments (Gonthier et al, 1997;Montoliu et al, 1995) and after long-term exposure to ethanol in rats (Bondy and Guo, 1995;Calabrese et al, 1998a,b;Montoliu et al, 1994;Rouach et al, 1997).…”
mentioning
confidence: 96%
“…However, direct neurotoxicity of ethanol on vermal granule cells and Purkinje cells has been demonstrated in animal experiments [11,33,39]. It appears that ethanol-induced neurotoxicity is mediated by oxidative stress and mitochondrial malfunction [11,13,25]. Likewise, studies in humans revealed biochemical alterations in brain tissue of chronic alcoholics most likely reflecting increased peroxide production [14].…”
Section: Introductionmentioning
confidence: 99%